Characteristics of gram-stained cervical smear from patients with Chlamydia trachomatis infection. - Raddi, M. S.; Vidal, A. F.; Santana, D. M. (My University, 1993)
Cervical discharges from 142 women attending the Public Gynecologic Service of Araraqura (SESA), Brazil were cultured for Chlamydia trachomatis. Gram-smears and plating on semiquantitative sheep blood agar and chocolate agar were also carried out. An isolation rate of 18% was reported. The presence of purulent cervical secretion was observed in 8 (32%) out of 25 women. It was also observed that a substantial proportion of culture-positive women had no symptoms. Our data demonstrate that screening tests should be based on specific diagnostic techniques for Chlamydia trachomatis since the majority of infected women we examined were asymptomatic.
Keywords: crystal violet; Gram's stain; phenazine derivative; Chlamydia trachomatis; chlamydiasis; female; human; isolation and purification; mass screening; microbiology; pregnancy; pregnancy complication; prevalence; uterine cervicitis; vagina smear; Cervicitis; Chlamydia Infections; Female; Gentian Violet; Human; Mass Screening; Phenazines; Pregnancy; Pregnancy Complications, Infectious; Prevalence; Support, Non-U.S. Gov't; Vaginal Smears